Time changes during the last 40 years in the Solfatara magmatic–hydrothermal system (Campi Flegrei, Italy): new conceptual model and future scenarios - L. Marini; L. Marini; C. Principe; C. Principe; M. Lelli; M. Lelli (Solid Earth)
We propose a new conceptual model of the Solfatara magmatic–hydrothermal system based on the results of new gas geoindicators (Marini et al., 2022) and the available geological, volcanological, and geophysical information from surface surveys and deep geothermal wells. Using the new gas geoindicators, we monitored the temperature and total fluid pressure over a time interval of ∼40 years: (i) in the shallow reservoir (0.25–0.45 km depth), where CO equilibrates; (ii) in the intermediate reservoir (2.7–4.0 km depth), where CH4 attains equilibrium; and (iii) in the deep reservoir (6.5–7.5 km depth), where H2S achieves equilibrium. From 1983 to 2022, the temperature and total fluid pressure of the shallow reservoir did not depart significantly from ∼220 °C, ∼25 bar, whereas remarkable and progressive increments in temperature and total fluid pressure occurred in the intermediate and deep reservoirs, with peak values of 590–620 °C, 1200–1400 bar in the intermediate reservoir and 1010–1040 °C, 3000–3200 bar in the deep reservoir, in 2020. Our new conceptual model allowed us to explain (a) the pressurization–depressurization of the intermediate reservoir, acting as the “engine” of bradyseism, and (b) the time changes of total fluid pressure in the deep reservoir, working as a temporary “on-off switch” of magmatic degassing. We also used our new conceptual model to infer, in the absence of external factors, the only two possible future scenarios which show that the pressurization of the intermediate reservoir might trigger a hydrothermal explosion. We further propose risk mitigation actions.